The ethical and legal framework for international tissue transfer - Lenk, Christian (Henry Stewart Talks, 2016)
No-property rule, The bundle theory of property, Commodification of body material, Damage by loss of biomaterial, Double character of body material, Anonymization and pseudonymization of body material and accompanying data, Donor information: specific vs. broad consent
Archived at 2022/03/30